Implementation of Knowledge Management in Improving Organizational Innovation and Performance in the Digital Era - Sirait, Ritawati; Sitanggang, Lestari Pratiwi; Simbolon, Oslan Juliana; Trisanti, Ayu; Br. Tarigan, Miska Irani (Sean Institute, 2025)
Digital transformation has encouraged organizations to optimize knowledge management (KM) as a strategy to improve innovation and performance. This study aims to analyze the role of knowledge management implementation in supporting innovation and organizational performance in the digital era through a literature review approach of fifteen national and international journals published between 2011 and 2025. The analysis was conducted by identifying research methods, variables, and key findings from each study, then synthesizing them to find patterns of relationships between KM, digitalization, innovation, and organizational performance. The results of the study indicate that KM processes including the creation, storage, sharing, and application of knowledge have a significant influence on increasing innovation, operational effectiveness, and the ability of organizations to adapt to changes in the digital environment. Digitalization acts as an enabler that strengthens KM implementation through information technology, digital collaboration systems, and data-based knowledge sharing mechanisms. Knowledge sharing culture and transformational leadership are also proven to be key determinants of KM success, while obstacles such as employee resistance and limited digital infrastructure are still frequently encountered. Overall, this study confirms that the integration of KM, digitalization, and an adaptive organizational culture is a strategic foundation for improving organizational innovation and performance in the digital era.